High-Attenuation Wideband Active Common-Mode EMI Filter Section - Zhang, Kun; Wang, Ke-Wei; Chung, Henry Shu-Hung (IEEE transactions on power electronics, 2022)
A high-attenuation wideband active common-mode filter (ACF) section is presented. Each section is composed of an active capacitor and a small common-mode (CM) inductor. The active capacitor is realized by using several coupling capacitors and a class-A bipolar-junction-transistor based amplifier for its low-cost, fast response, and good immunity to high voltage transients. The structure of the amplifier consists of a common-collector amplifier and a high-gain common-emitter amplifier with an active load. The working bandwidth of the ACF ranges from 150 kHz to 30 MHz. By cascading several ACF sections, a multistage structure that exhibits high filtering attenuation can be designed. The number of cascaded sections is optimized by considering the required filtering attenuation. The performance of single-stage and multistage ACFs is evaluated on two commercial power supplies with rated power of 90 and 1000 W, respectively. The CM noise of the power supplies with the proposed ACF and with the original passive filters is compared. The results show that the physical volume of the ACF is significantly smaller than that of the passive filter, and the power dissipation of the ACF is similar to that of the passive filter.